Mathematical analysis : business and economic applications - Weber, Jean E. (New York : Harper & Row, 1976)
The text offers the students an understanding of quantitative techniques both in their mathematical context and as they are applied to business and economic problems.
Includes index.
Bibliography: p. 679-681.
rpm 14/09/2017
Loans
Keywords: Business mathematics; Mathematical analysis; Economics, Mathematical